A Legal Appraisal of the Nigerian Communication Commission’s Registration of Telephone Subscribers Regulation (RTS) 2011: Issues and Challenges - Bello, Sani Rabiu; Abubakar, Mohammed (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2024)
This paper sought to appraise the Nigerian Communication Commission Registration of Telephone Subscribers (RTS) Regulation 2011 with a view to reveal its challenges. The Nigerian Communication Commission compels its licensees to register their new, existing and foreign subscribers’ personal information utilizing their medium to the government central database. The regulation made provision to promote constitutional rights to privacy, freedom of expression and electronic data protection. Having perused the regulation and accessing scholarly works on doctrinal methodology of research, it reveals that the regulation though logically sound, the motive for law enforcement and counter terrorism on the part of government was over emphasized. We discovered privacy infringement, implementation gap and few section of the society were discriminated due to limited access to enrolment facilities. Consequently re-regulation, active implementation and policy on massive digital inclusion were recommended among others.